PENGARUH DAYA TARIK RASIONAL DAN EMOSIONAL PADA IKLAN YOUTUBE TERHADAP MINAT BELI DENGAN KESADARAN MEREK SEBAGAI VARIABEL MEDIASI (Studi pada Iklan YouTube Pantene ‘Bye #RambutCapek Hello #RambutKeCharged’) - Anindita Heningdrapraja; Susilo Toto Rahardjo (Diponegoro Journal of Management, 2022)
This study aims to examine a conceptual model of rational and emotional attractiveness in influencing purchase intention by using brand awareness as an intermediary. The problem in this study is how to use variables in the Elaboration Likelihood Model (ELM) theory to increase purchase intention. The sample used in this study was 167 residents domiciled in DKI Jakarta with an age range of 20-34 years who had seen/watched the Pantene advertisement 'Bye #RambutCapek Hello #RambutKeCharged' on the Pantene YouTube channel. This research method uses Structural Equation Model (SEM) analysis with AMOS as a data processing tool. Based on the results of the study, it was found that rational appeal, emotional appeal, and brand awareness have a positive and significant effect on purchase intention. Therefore all hypotheses in this study were accepted. This study also proves that brand awareness is able to mediate the relationship between rational and emotional attractiveness to purchase intention.